Florida’s Established Arthropod Weed Biological Control Agents and Their Targets - James P. Cuda; J. Howard Frank (EDIS)
Around 5% of the plant species deliberately introduced into Florida for crop production and horticultural uses have invaded sensitive aquatic and terrestrial natural areas as well as improved pastures. One of the reasons they become invasive is they lack the natural enemies that limit their reproduction. Biological control reunites these natural enemies (usually arthropods) with their host plants to selectively weaken and suppress the invasive weeds. This 3-page fact sheet was written by J. P. Cuda and J. H. Frank and published by the UF Department of Entomology and Nematology, October 2012.